Piles Pullout Enhancement Subjected to Inclined Loads - Aljuboori, Wisam A.; Al-Saidi, Aamal A. H. (Civil Engineering Journal, 2025)
This study focuses on the experimental and numerical analysis of pullout resistance for a single pile subjected to inclined loads in sandy soil, both before and after improvement with asphalt enhancement. The sandy soil, characterized by low cohesion, poses significant challenges for foundation stability under vertical and inclined loading conditions. Pullout tests were conducted experimentally at angles of 0°, 30°, 45°, 60°, and 90° for both vertical and horizontal components of inclined loads using a custom-designed testing setup. Cutback asphalt was introduced as an improvement agent. The experimental results revealed a significant reduction in displacement up to 62% and an improvement in pullout resistance for the asphalt-treated soil up to 55% and 72% for vertical and horizontal load directions, respectively. PLAXIS software was validated through numerical modeling, which confirmed the improved load-displacement behavior and stress distribution. The asphalt enhancement demonstrated an improvement in pullout resistance, underscoring its effectiveness in creating a cohesive soil matrix that enhances load transmission and reduces void ratios. This research provides valuable insights into the load’s inclination and improvement with angle variations; the pullout capacity enhanced significantly with the inclination angle with vertical due to the formation of a bigger failure zone, thus offering practical solutions for improving the performance of pile-supported foundations in weak sandy soils under challenging inclined load conditions.